DIGITAL GAME-BASED LANGUAGE LEARNING: ENHANCING GRAMMAR AND LISTENING SKILLS - Jumaniyazova Lobar Sirojiddin qizi (TADQIQOTLAR, 2025)
Digital Game-Based Language Learning (DGBLL) has emerged as a dynamic pedagogical approach, integrating interactive digital games into language instruction to foster learner engagement and improve linguistic competencies. This paper explores the efficacy of DGBLL in enhancing grammar and listening skills among English as a Second Language (ESL) learners. Drawing upon recent empirical studies, the discussion highlights how digital games can provide contextualized grammar practice and immersive listening experiences, leading to improved language acquisition. The paper also examines learner attitudes towards DGBLL, the role of gamification in motivation, and the implications for curriculum design. Findings suggest that when effectively implemented, DGBLL can significantly contribute to the development of grammar and listening skills, offering a complementary tool to traditional language teaching methods.